Cardiotoxicity of Anthracyclines - Cardinale, Daniela; Iacopo, Fabiani; Cipolla, Carlo Maria (Frontiers in Cardiovascular Medicine, 2020)
Cardiotoxicity is a feared side effect that may limit the clinical use of anthracyclines. It may indeed affect the quality of life and survival of patients with cancer, regardless of oncological prognosis. This paper provides an overview of anthracycline-induced cardiotoxicity in terms of definition, classification, incidence, risk factors, possible mechanisms, diagnosis, and treatment. We also report effective strategies for preventing cardiotoxicity. In addition, we discuss limiting current approaches, the need for a new classification, and early cardiotoxicity detection and treatment. Probably, anthracycline-induced cardiotoxicity is a continuous phenomenon that starts from myocardial cell injury; it is followed by left ventricular ejection fraction (LVEF) and, if not diagnosed and cured early, progressively leads to symptomatic heart failure. Anthracycline-induced cardiotoxicity can be detected at a preclinical phase. The role of biomarkers, in particular troponins, in identifying subclinical cardiotoxicity and its therapy with angiotensin-converting enzyme inhibitors (mainly enalapril) to prevent LVEF reduction is a recognized and effective strategy. If cardiac dysfunction has already occurred, partial or complete LVEF recovery may still be obtained in case of early detection of cardiotoxicity and prompt heart failure treatment.